A psychodynamic view to alcohol dependency - Göka, Erol; Başterzi, Ayşe Devrim (Journal of Dependence, 2001)
Alcohol dependency is accepted as a heterogenous and multifactorial etiological disease. The combinations which were changed according to needs of each patient and contain the psychodynamic-oriented approaches have been tried in the treatment. The principles of psychodynamics related to the psychodynamic- oriented individual psychotherapy for alcohol dependency should be reviewed. Many ideas about dependency were suggested. The differential diagnosis and the comorbid psychiatric states and the physical diseases should be detected before starting the individual therapy. This evaluation should be performed after the withdrawal period for6 and 8 weeks. The individual psychodynamic-oriented psychotherapy can only be used with the other treatment modalities in the treatment of alcohol dependency. But the classical psychoanalytical treatment is contraindicated in this field. The most important indication for the psychodynamic-oriented individual psychotherapy is existence of an intrapsychic confliction.Aim of the treatment contract should be determined as abstinency. The treatment contains the levels for "I can't drink", "I won't drink", "I don't drink" and "I can return back to the social drinking". Transference and counter-transference are interpreted in this period. As a conclusion, choice of psychodynamic-oriented psychotherapy should be considered in the treatment of alcohol dependency as well as other many treatment methods.
Keywords: Alcohol dependency; psychodynamic approach; psychotheraphy